Pemberdayaan Pemuda Karang Taruna Melalui Program Remaja Pintar Berbasis Agama Desa Wisata Kandri Kota Semarang - Muslam, Muslam; Fatkuroji, Fatkuroji; Muntoli'ah, Muntoli'ah (Dimas: Jurnal Pemikiran Agama untuk Pemberdayaan, 2016)
This accompanying outreach youth "Gerak Maju" in the tourist village Kandri Gunungpati Semarang city in plays an active role in taking the role of and participation in activities in the village tour kandri potentialities and promote tourism as one of the tourist icon in the city of Semarang in addition to tourist village Mijen and Nongkosawit. Public service aims to help resolve the problems experienced by Youth of Gerak Maju, in relation to some business skills and the development of the field of the internet as a promotional event or marketing tourism village.The problems experienced by youth were prepared in a group organization to fill the business activities and promote tourism but will not yet have expertise in creative businesses and information technology so that its activities have not been able to program along with the villages that have been elevated to the Government program of the city of Semarang.Solutions offered in the program of this devotion is to provide Entrepreneurship Training In Graphic Design, Syar'iah, usinh Weblog, techniques for embroidery ribbons, and marketing through the internet with emphasis on the promotion of the tourist potentialities that have been developed. Benchmark the success of this activity is the formation of a group/individual creative effort that Syar'iah as well as the availability of a set of media for promotion through the internet as well as the ability of the youth in the market. Benchmark the success of this activity is the formation of a group/individual creative effort that Syar'iah as well as the availability of a set of media for promotion through the internet as well as the ability of the youth in the market potential of the flagship through the internet. And also offers in depth Training in the form of approach to Entrepreneurship In Syar'iah, skilled In Entrepreneurship Syar'iah, graphic design, using Graphic Design create a Weblog, and manage Weblog website globally.Â Pengabdian masyarakat ini mendampingi pemuda karang taruna â€œGerak Majuâ€ di desa wisata Kandri Gunungpati Kota Semarang dalam berperan aktif dalam mengambil peran dan partisipasi dalam kegiatan di desa wisata kandri serta mempromosikan potensi-potensi desa Wisata tersebut sebagai salah satu icon wisata di kota Semarang selain desa wisata Mijen dan Nongkosawit. Pengabdian masyarakat ini bertujuan untuk membantu menyelesaikan permasalahan yang dialami Pemuda Karang Taruna Gerak Maju, dalam kaitannya dengan beberapa ketrampilan usaha dan pengembangan bidang internet sebagai ajang promosi atau pemasaran desa wisata.Permasalahan yang dialami adalah pemuda karang taruna telah siap secara kelompok organisasi untuk mengisi kegiatan usaha dan mempromosikan desa wisata akan tetapi belum memiliki keahlian dalam usaha kreatif dan teknologi informasi sehingga kegiatannya belum mampu seiring dengan program desa wisata tersebut yang telah diangkat menjadi program pemmerintah kota Semarang.Solusi yang ditawarkan dalam program pengabdian ini adalah Memberikan pelatihan Berwirausaha Secara Syarâ€™iah, Desai Grafis, membuar Weblog, Teknik Sulam Pita, dan pemasaran melalui internet dengan menekankan pada promosi potensi-potensi wisata yang telah dikembangkan. Tolak ukur keberhasilan kegiatan ini adalah terbentuknya kelompok/individu usaha kreatif yang Syarâ€™iah serta tersedianya seperangkat mediaÂ  untuk promosi melalui internet serta kemampuan para pemuda dalam memasarkan potensi unggulan melalui internet. Dan juga menawarkan pendekatan berupa Pelatihan secara mendalam untuk Berwirausaha Secara Syarâ€™iah, terampil mem Berwirausaha Secara Syarâ€™iah, Desain Grafis, membuar Weblog buat Desai Grafis, membuar WeblogÂ  serta mengelola website secara global.